2011
DOI: 10.1016/j.ccc.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Therapy for Acute Lung Injury and Acute Respiratory Distress Syndrome

Abstract: This article examines exogenous lung surfactant replacement therapy and its utility in mitigating clinical acute lung injury (ALI) and the acute respiratory distress syndrome (ARDS). Biophysical research has documented that lung surfactant dysfunction can be reversed or mitigated by increasing surfactant concentration, and multiple studies in animals with ALI/ARDS have shown that respiratory function and pulmonary mechanics in vivo can be improved by exogenous surfactant administration. Exogenous surfactant th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
85
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 267 publications
(210 reference statements)
0
85
0
9
Order By: Relevance
“…Although some early SRT large-animal and adult clinical trials were successful (5)(6)(7)(8), subsequent studies were failures (9)(10)(11). The field is looking for direction, with concerns ranging from the delivered surfactant biochemistry to the persistence of the underlying ARDS disease to the adequacy of delivery (12). The model presented here addresses the delivery issue and shows that simulations of these adult SRT studies produce significantly different delivery distributions that can explain success vs. failure.…”
mentioning
confidence: 96%
“…Although some early SRT large-animal and adult clinical trials were successful (5)(6)(7)(8), subsequent studies were failures (9)(10)(11). The field is looking for direction, with concerns ranging from the delivered surfactant biochemistry to the persistence of the underlying ARDS disease to the adequacy of delivery (12). The model presented here addresses the delivery issue and shows that simulations of these adult SRT studies produce significantly different delivery distributions that can explain success vs. failure.…”
mentioning
confidence: 96%
“…Improvement in ventilation characteristics were noted in several nonrandomised trials of exogenous surfactant therapy in children with ARDS [55], although the number of patients in each study were small. Overall, there seem to be short-term benefits in exogenous surfactant, although further larger trials are warranted.…”
Section: Surfactant Use In Childrenmentioning
confidence: 99%
“…Decreases in surfactant production induced by prematurity or disease cause alveolar collapse, hypoxemia and reductions in lung compliance, thereby requiring greater distending pressures to inflate the lung and increases in the work of breathing 2. Prior studies dating back >30 years have shown that alveolar hypocapnia causes depletion of lamellar bodies in ATII cells and decreases surfactant production 3.…”
mentioning
confidence: 99%